The Role of Epidermal Growth Factor Receptor in the Management of Gastrointestinal Carcinomas: Present Status and Future Perspectives - Quasir Mahmood, Malik; Dhar Shukla, Shakti; Dua, Kamal; D. Shastri, Madhur (Current Pharmaceutical Design, 2017)
Background: The global burden of gastrointestinal cancers, including colorectal, stomach, and esophageal cancers is rising steadily. Several therapeutic approaches have been considered for the treatment of GI carcinomas. However, none showed to halt or cure the disease. There is a need to develop effective targeted molecular therapies; mainly to overcome the adverse effects of currently used treatment regimens, as well as, to benefit a large proportion of cancer patients who do not respond well to chemotherapeutics. Methods: Epidermal growth factor receptor (EGFR) is one of the promising targets for cancer therapy. Through a cascade of events, activation of EGFR plays an important role in the homeostasis and pathogenesis of various disorders, including carcinomas of the gastrointestinal (GI) tract, ranging from oesophagitis to complex colon carcinoma. Results: The GI carcinomas are associated with aberrant EGFR expression. In this review, emphasis was made on various EFGR-associated signalling pathways, their mechanisms and role in the formation of gastrointestinal lesions. Conclusion: The current EGFR-targeting therapeutics and an outline of various novel drug delivery systems that could potentially be employed for targeting EGFR during cancer treatment were discussed. This would help medical, pharmaceutical and other life science researchers in providing broad understanding of the work previously conducted in this field.
Keywords: gastrointestinal carcinomas